The Cambridge handbook of psychology and economic behaviour - Lewis, Alan, 1952- (Cambridge handbooks in psychology., 2008)
Employing empirical methods, including laboratory experiments, field experiments, observations, questionnaires and interviews, the Handbook covers aspects of theory and method, financial and consumer behaviour, the environment, and biological perspectives.